Hit or Miss: What Leads Experts to Take Advice for Long-Term Judgments? - Ecken, Philipp; Pibernik, Richard (Management Science, 2016)
Managers and policy makers frequently face crucial strategic decisions that inevitably rely on judgments about relevant future events. These judgments are often characterized by very high uncertainty and the absence of experience from previous good or bad judgments. Judgments of other experts are oftentimes an important—sometimes the only—source of additional information to reduce uncertainty and improve judgment accuracy. However, in many practical situations, decision makers have very limited means to evaluate the quality of such “advice” from other experts and could tend to ignore this valid source of information. In this paper, we study what leads decision makers to take advice from an expert panel when judging the probability of far-future events with high economic impact. Our analysis is based on a unique data set that comprises more than 15,000 advice-taking decisions made by almost 1,000 experts from different industries. We find that decision makers have a strong tendency to ignore advice, which pronounces even further when conflicts in terms of beliefs, past experiences, or desires arise. This paper was accepted by Yuval Rottenstreich, judgment and decision making.